Exploring the cooperation between nitrogen-fixing and non-fixing alfalfa rhizobia - Brambilla, Silvina Maricel; Liebrenz, Karen Ivana; Odorizzi, Ariel; Arolfo, Valeria; Maguire, Vanina Giselle; Moreno, Maria Valeria; Ruiz, Oscar Adolfo; Stritzler, Margarita; Serantes, Maria Laura; Soto, Gabriela Cynthia; Ayub, Nicolás Daniel (Springer, 2024)
Alfalfa plays a crucial role in agriculture due to its nitrogen-fixing partnership with rhizobia, resulting in nutritious forage. While the potential parasitic action of inefficient rhizobia has been extensively studied, little attention has been given to how these inefficient strains can cooperate with highly efficient nitrogen-fixing rhizobia. In this brief article, we explored the cooperation between nitrogen-fixing and non-fixing alfalfa rhizobia. Genomic, genetic, and physiological analyses suggest that the presence of the NO-detoxifying enzyme HmpA in inefficient rhizobia plays a crucial role in alleviating host-derived nitrosative stress within mixed nodules. This process enhances the fitness of efficient rhizobia, consequently improving their capacity for plant growth promotion activities. Finally, we discussed the biotechnological implications of these results for inoculant production and the possible role of the hmpA gene in the mixed infections of plants and animals by beneficial and pathogenic bacteria.